Hydrogeochemical characteristics of the River Sava watershed in Slovenia - Kanduč, Tjaša; Ogrinc, Nives (Geologija, 2007)
The River Sava is a typical HCO3- - Ca2+ - Mg2+ River. Total alkalinity increases in the part of the watershed composed of carbonate and clastic rocks, which are less resistant to weathering processes. Ca2/Mg2+ ratios are around 2 in the carbonate part of the watershed and increase in the watershed composed of carbonate and clastic rocks, indicating dissolution of calcite with magnesium. According to PHREEQC for Windows calculations, the River Sava and its tributaries are oversaturated with respect to calcite and dolomite. δ18OH2O and δDH2O are related to the meteorological patterns in the drainage basin. River water temperatures fluctuate annually following air temperatures. The relationship between the temperature and δ18OH2O and δDH2O values primarily reflects the strong dependence of δ18O and δD on precipitation and evaporative enrichment in heavy oxygen and hydrogen isotopes of infiltrating water recharging the River Sava from its slopes. The δ13DIC values are controlled by processes in the terrestrial ecosystem and stream processes such as: (1) dissolution of carbonates, (2) soil derived CO2, and (3) equilibration with atmospheric CO2. Lower δ13DIC values are observed in the spring sampling season due to abundant precipitation related to soil leaching of CO2 in the river system. From discharge and concentration measurements of sulphate and according to the drainage area of the River Sava basin, the annual sulphur flux at the border with Croatia was estimated to be 1.4 x 107 g SO4/km2. Assuming that the sources of SO42- to the Sava are its tributaries, precipitation and other sources, the contributions of these inputs were calculated according to steady state equations and estimated to be 52 : 8 : 40 %, respectively. Other sources are attributed to human influences such as industrial pollution and oxidation of sulphides.